2016
DOI: 10.1111/dth.12379
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive therapy in the posttransplant period and skin cancer

Abstract: The preliminary results indicate that the risk of NMSC in RTRs is significantly higher than in the general population and thus emphasize the need to improve preventive strategies in the Czech transplant population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 11 publications
0
11
1
Order By: Relevance
“…The use of ciclosporin A has been reported as ineffective in two patients . Given the risk of skin cancer associated with both NS and ciclosporin A, we do not recommend using it (LoE 3, GoR D). Systemic immunoglobulins have been reported as safe and effective in five patients, but there is limited evidence to recommend them for long‐term treatment (LoE 3, GoR D).…”
Section: Particularities Of Congenital Ichthyosismentioning
confidence: 99%
“…The use of ciclosporin A has been reported as ineffective in two patients . Given the risk of skin cancer associated with both NS and ciclosporin A, we do not recommend using it (LoE 3, GoR D). Systemic immunoglobulins have been reported as safe and effective in five patients, but there is limited evidence to recommend them for long‐term treatment (LoE 3, GoR D).…”
Section: Particularities Of Congenital Ichthyosismentioning
confidence: 99%
“…Although skin cancers are known to be associated with immunosuppressive therapy, there are no conclusive data on the extent of the risk associated with each immunosuppressive drug. Several studies on heart, liver, and kidney transplant patients have shown a higher risk of skin cancers when calcineurin inhibitors are used 35‐37 . As far as antimetabolites are concerned, azathioprine has frequently been associated with a higher risk of skin cancers while mycophenolate mofetil seem to play a more controversial role 38‐40 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on heart, liver, and kidney transplant patients have shown a higher risk of skin cancers when calcineurin inhibitors are used. [35][36][37] As far as antimetabolites are concerned, azathioprine has frequently been associated with a higher risk of skin cancers while mycophenolate mofetil seem to play a more controversial role. [38][39][40] On the other end of the spectrum, mTOR inhibitors have been reported to lower the risk of skin cancers as opposed to other immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%
“…54 Another retrospective study of 797 RTRs reported that the risk of NMSC was significantly higher in patients receiving ATG compared with anti-CD 25 monoclonal antibody [Standardized morbidity ratio (SMR) = 4.14; 95% CI = 2.05-7.56, p = .000 for ATG and SMR = 2.02; 95% CI = 0.46-6.48, p = .293 for anti- CD 25]. 56 Based on existing data, long-term immunosuppressive medications used in the maintenance phase is also likely to be oncogenic.…”
Section: Oncogenic Effects Of Immunosuppressantsmentioning
confidence: 99%
“…Although there is no adequate evidence to recommend a specific interval of full skin examination, post-transplant skin cancer surveillance guidelines in Europe and United States advise full skin examination of SOTRs every 6-12 months in a specialist clinic. [55][56][57] Harwood et al provided a sensitive, practical and targeted algorithmic approach to define individual risk and calculate appropriate skin cancer surveillance intervals for detection of NMSC in SOTRs. 10 The frequency of examination should depend on the individual risks as proposed in Table 3 to identify precursors of skin cancers and early detection of skin carcinoma.…”
Section: Skin Cancer Surveillance and Prevention Programmentioning
confidence: 99%